2009
DOI: 10.1111/j.1349-7006.2009.01362.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E succinate induced apoptosis and enhanced chemosensitivity to paclitaxel in human bladder cancer cells in vitro and in vivo

Abstract: There have been several studies on the antitumor activities of vitamin E succinate (a-TOS) as complementary and alternative medicine. In the present study, we investigated the cytotoxic effect of a-TOS and the enhancement of chemosensitivity to paclitaxel by a-TOS in bladder cancer. and 5637 bladder cancer cell lines were cultured in a-TOS and ⁄ or paclitaxel in vitro. Cell viability, flow cytometric analysis, and nuclear factor-kappa B (NF-jB) activity were analyzed. For in vivo therapeutic experiments, pree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…The cytotoxicity of HA-VES copolymers could be attributed to the function of VES, which is to selectively induce apoptosis and inhibit the proliferation of tumor cells without any cytotoxic effects on normal cells. 25,28 Moreover, enhanced cytotoxicity was observed with increase of DS, especially of HA-VES12, due to more VES existing in high DS of HA-VES12. Therefore, synthetic copolymers of HA-VES with different DS have selective antitumor abilities and could exert antitumor effects.…”
Section: In Vitro Cytotoxicity Cytotoxicity Of Ha-ves Copolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…The cytotoxicity of HA-VES copolymers could be attributed to the function of VES, which is to selectively induce apoptosis and inhibit the proliferation of tumor cells without any cytotoxic effects on normal cells. 25,28 Moreover, enhanced cytotoxicity was observed with increase of DS, especially of HA-VES12, due to more VES existing in high DS of HA-VES12. Therefore, synthetic copolymers of HA-VES with different DS have selective antitumor abilities and could exert antitumor effects.…”
Section: In Vitro Cytotoxicity Cytotoxicity Of Ha-ves Copolymersmentioning
confidence: 99%
“…25,26 VES, not other vitamin E derivatives, has anticancer properties against multiple cancer cells and nontoxic side effects on normal cells, due to increased generation of reactive oxygen species inducing membrane-destabilizing properties in the tumor cells by VES. [26][27][28] Based on the hydrophobicity and synergistic antitumor effects of VES, a functional copolymer, with VES as the hydrophobic group and HA as the hydrophilic part, has been designed which acts as a nanocarrier for the delivery of antitumor drugs. 29 In this study, to integrate CD44 receptor-mediated active targeting effects of HA and synergistic antitumor effects of VES, the copolymers of HA-ethylenediamine-VES (called HA-VES) with different degrees of substitution (DS) were synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also shown that α-TOS inhibits tumor cell growth by a variety of mechanisms, including DNA synthesis arrest, cell cycle blockade, induction of apoptosis, inhibition of tumor cell proliferation and differentiation, as well as inhibition of angiogenesis (24,29,(44)(45)(46). This analogue kills cells via apoptosis and affects expression of genes involved in cell proliferation and cell death in a sub-apoptotic manner during the cell cycle (23).…”
Section: ␣-Tos and Apoptogenic Propertiesmentioning
confidence: 95%
“…It has been widely reported that α-TOS and its analogs possess anticancer properties against a wide variety of human cancer cells while remaining nontoxic to normal cells ( Figure S5). 17 Mi et al reported the synergistic effect of T2K and DTX. 23 The same conclusion could also be drawn from the cytotoxicity of DTX-loaded TGK micelles and T2K micelles (Figure 7).…”
Section: In Vitro Cytotoxicitymentioning
confidence: 99%
“…16 Second, TPGS also acts as an anticancer agent inducing apoptosis and producing a synergistic effect with other anticancer agents. 17 d-α-Tocopherol succinate (α-TOS) and its analogs can induce reactive oxygen species generation, subsequently inducing apoptosis in cancer cells while being nontoxic toward normal cells. 18,19 TPGS has also been approved by the US Food and Drug Administarion as a safe pharmaceutical adjuvant used in drug formulation.…”
Section: Introductionmentioning
confidence: 99%